2016
DOI: 10.1108/ijwbr-09-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

A personality-based measure of the wine consumption experience for millennial consumers

Abstract: Purpose This paper aims to propose a personality-based approach to measure Millennial consumers’ wine evaluations. Past personality-based measures (brand personality, country personality and product personality) each presents their own issues when it comes to measuring wine perceptions, especially those of neophyte wine consumers. This paper proposes a new, holistic and tailored measure to gauge the personality dimensions Millennials perceive in wine. Design/methodology/approach Multiple studies were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…Also, with the current interest in defining consumer segmentation, demographic aspects such as gender and those based on knowledge and interest in the world of wine were investigated. Thus, some studies have shown how young people's wine choices are fundamentally influenced by extrinsic type factors (bottling, labelling, and design) rather than by the characteristics of the product itself (producer, country of origin, type of wine, graduation, quality or solera) [15,26]. Even women give greater importance to the external signals of the wine than to the internal ones, according to Bruwer and McCutcheon [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, with the current interest in defining consumer segmentation, demographic aspects such as gender and those based on knowledge and interest in the world of wine were investigated. Thus, some studies have shown how young people's wine choices are fundamentally influenced by extrinsic type factors (bottling, labelling, and design) rather than by the characteristics of the product itself (producer, country of origin, type of wine, graduation, quality or solera) [15,26]. Even women give greater importance to the external signals of the wine than to the internal ones, according to Bruwer and McCutcheon [42].…”
Section: Discussionmentioning
confidence: 99%
“…In short, they are more involved in the decision process before making a purchase, and will, therefore, be guided by higher marks [44][45][46]48]. Concerning the search for information, Millennials have demonstrated active participation in activities related to wine, such as the search for emotional, experimental and educational value [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wine as a complex consumer product Wine is often defined as a complex product (Bruwer et al, 2011;Muelleret al, 2011;Ferro and Amaro, 2018;Lai, 2019) that goes beyond a mere consumer good but requires an understanding of how it is perceived and consumed, including influences such as culture, history, identity, value and socialization. Early this century, several researchers have attempted to make sense of these many factors that determine the consumer experience and then drill down into different consumer groups and their unique preferences IJWBR 32,3 (Hammond et al, 2013;Lategan et al, 2017;Spielmann et al, 2016). Popular factors were the different taste and visual aspects of the wine and correlating it with gender, age and experience (Bruwer et al, 2011), others have explored the factors that affect wine purchasing behaviour such as the location and environment when purchasing or consuming wine (Bruwer and McCutcheon, 2017) and others again compared the findings across countries (Mueller et al, 2011).…”
Section: Literaturementioning
confidence: 99%
“…Nesta perspectiva, o vinho tem sido objeto de estudo em identidade pelos pesquisadores, os quais investigaram o envolvimento e o autoconceito em contextos situacionais com a bebida (Roe & Bruwer, 2017); o "coorte" etário e a sociodemografia entre idosos e jovens, em que as compras de vinhos especiais aumentam em razão do envelhecimento do indivíduo (Bruwer & McCutcheon, 2017); a formação identitária de consumidores em face a influência de atributos como a marca, altos preços, ponto de venda (não)tradicional, gostos, categoria de luxo e local de origem (Higgins & Wolf, 2016;Spielmann et al, 2016); e a influência do estilo de vida e dos contatos socioculturais, mediante ao forte envolvimento com o vinho na construção da identidade do consumidor (Rössel & Pape, 2016;Ritchie, 2007).…”
Section: Introductionunclassified